BARRIERS AND SUPPORT SYSTEMS FOR EXCLUSIVE BREASTFEEDING AMONG WORKING MOTHERS IN INDONESIA: A SOCIO-CULTURAL AND POLICY PERSPECTIVE (Proceedings of the International Conference on Public Health, 2025)
Despite the well-documented health benefits of breastfeeding for both mothers and infants, reintegration into the workforce postpartum presents a significant challenge. WHO (2023) stated that only 20% of countries worldwide require employers to provide paid maternity leave and facilities for breastfeeding or expressing breast milk. A rapidly growing female labor force participation rate exceeding 38.98% in Indonesia makes fostering supportive workplace environments critical. This study investigates the role of workplace social support in promoting breastfeeding practices among working mothers in Indonesia. This qualitative literature review employed Scopus, Science Direct, ProQuest, Google Scholar, and Crossref to understand essential forms of workplace breastfeeding social support, through the keywords “social support" and “exclusive breastfeeding” and workplace and "working mothers" and Indonesia. A comprehensive search of relevant databases yielded 1145 articles. Through a rigorous selection process, 23 articles were identified, published between 2012 and May 2024, comprising 11 quantitative and 12 qualitative studies. The primary barriers to breastfeeding in the workplace are: 1) lack of lactation facilities, 2) insufficient workplace support, and 3) unsupportive workplace policies. The review identified three crucial categories of workplace social support: informational support (providing access to lactation consultants, educational materials, and current information), instrumental support (implementing formalized breastfeeding policies, dedicated lactation facilities, extended maternity leave, flexible work arrangements, workload adjustments, and childcare options near workplaces), and peer support (facilitating participation in breastfeeding support groups and fostering communication networks among mothers). By implementing comprehensive social support, workplaces can empower working mothers to provide breast milk for their infants. Workplaces should provide dedicated facilities and resources to support mothers in nursing or expressing breast milk, fostering an environment that promotes exclusive breastfeeding among working mothers. Limitation: this article is a secondary review that relies on the quality of existing studies, although the studies were conducted through a rigorous selection process.
Keywords: Social support; exclusive breastfeeding; working mothers; workplace; socio-cultural barriers; policy implications